Addressing Small Scale Fisheries Management through Participatory Action Research (PAR), an Experience from the Philippines - Lutgarda L. Tolentino; Lily Ann D. Lando; Len R. Garces; Maripaz L. Perez; Claudia B. Binondo; Jane Marina Apgar (International Journal of Agriculture System, 2015)
This case demonstrates the potential of addressing small scale fisheries management through participatory action research (PAR) in one of the CRP 1.3/AAS sites in the Philippines. Following the iterative process of PAR, a series of focus group discussions (FGDs) to reflect on the issues and concerns of small scale fishermen (SSF) in Barangay Binitinan, Balingasag, Misamis Oriental, Philippines was carried out from February to May, 2014. This was followed by the conduct of consultative workshop among stakeholders in SSF in June 2014, the main objective of which was to develop a collective action plan for the management of said resource. The FGDs employed facilitated iteration and reflection of issues affecting various groups of small scale fishing community, while the Consultative Workshop among stakeholders used the appreciation-influence-control model of participatory stakeholder engagement (Ratner 2011).Consequently, various stakeholders of small scale fisheries begin to understand, appreciate and take actions together. A feeling of trust and confidence among them begin to develop which enabled them to craft a collective action plan on sustainable management and governance of municipal waters and fisheries resources. Aside from these outcomes, these processes led to the admission of “sahid” (beach seine) operators that they are indeed using illegal gear, that their gear would be replaced by the legal one by the Bureau of Fisheries and Aquatic Resources (BFAR), that the Law Enforcers would implement the Law and the small scale fishermen would abide the rules and would be apprehended by Law Enforcers once they violate the rules and the LGUs asking stakeholders to feedback the amendments necessary to make municipal ordinances well fitted to them. Another major outcome of these processes was the identification of research topics which the stakeholders identified to be necessary so that science-based productivity and governance decisions can be put in place. All of these activities fall within the PAR processes.